The social stratification of social risks - Herman Deleeck Centre for Social Policy, Antwerp; Pintelon, Olivier; Cantillon, Béa; Van den Bosch, Karel; Whelan, Christopher T. (Antwerp, 2011)
"This paper investigates how social class shapes the occurrence of social risks, defined as socio-economic circumstances associated with significant losses of income. The motivation for this exploration derives from the ‘individualisation thesis’, which calls into question the structuring impact of social class. At the same time, social policy discourse has, under the mantra of ‘social investment’, undergone significant change, with greater emphasis being placed on individual responsibility. Hence it is important to ascertain whether intergenerational class effects (continue to) exist. Using SILC 2005 data, we consider their impact on a relevant selection of social risks: unemployment, ill-health, living in a jobless household, single parenthood, temporary employment, and low-paid employment. A pooled country model is estimated for the purpose of assessing social background effects. The results provide clear evidence of a continuing influence of social class (of origin)."